Attractant Pheromone of the Neotropical Species Neomegalotomus parvus (Westwood) (Heteroptera: Alydidae) - Raul Alberto Laumann; Miguel Borges; Jeffrey R. Aldrich; Ashot Khrimian; Maria Carolina Blassioli-Moraes (Psyche: A Journal of Entomology)
The Neotropical broad-headed bug, Neomegalotomus parvus (Westwood), is adapted to various leguminous crops and is considered a pest in common bean and soybean. The chemical communication of this species was studied in order to identify an attractant pheromone. Males and females of N. parvus produce several short-chain esters and acids, and their antennae showed electrophysiological responses to five of these compounds, three common to both sexes (hexyl butanoate, 4-methylhexyl butanoate, and hexyl hexanoate), and two female-specific compounds (4-methylhexyl pentanoate and hexyl pentanoate). Both aeration extracts of females and a solution containing five synthetic compounds mimicking the natural blend were attractive to males and females N. parvus in a laboratory bioassay. Aspects of the chemical ecology of the broad-headed bugs and the possibility to use pheromone-baited traps in the field for monitoring are discussed.